(untitled) (Web of Teachers: Inderscience Research, 2024)
The article discusses the importance of using new pedagogical technologies in teaching English, taking into account the somewhat complex nature of mastering the subject, analyzes all the possibilities of the student. Also, examples of new methods in language development are given, and their importance is revealed.